Photography Terms In Understanding Exposure And Their Translations - Ronald Umbas (Program Magister Linguistik Universitas Udayana, 2017)
This article aims to analyze the translation procedures adopted in translating photography terms from English into Indonesian. The data were taken from the book entitled Understanding Photography (Peterson, 2010) and its Indonesian version Pintar Eksposur (Andwiani, 2013). The data in this qualitative research were collected using note-taking technique. The analyzed data were presented informally and formally. The theory used to analyze the problems and what procedures were applied in translating photography terms from English into Indonesians and why those procedures were applied were the theory and procedures proposed by Newmark (1988) who presented eighteen translation procedures. There were five translation procedures applied in translating the photography terms including the literal, transference, naturalization, functional equivalent, and couplet procedures.